Neuropsychological profile of children with dyslalias: Memory impairment and attentional. - Conde-Guzón, Pablo; Quirós-Expósito, Pilar; Conde-Guzón, María J.; Bartolomé-Albistegui, María T. (Anales de Psicología / Annals of Psychology, 2014)
In this study we investigate the neuropsychological functioning of children with dyslalias. 34 children with multiple dyslalia (articulatory distortion or substitution of three phonemes: / r /, / l / and / s /) and normal neurological examination. 28 children without speech problems are used as reference group. The neuropsychological profile is estimated using the Wechsler Intelligence Scale for Children-Revised (WISC-R) and Luria Neuropsychological Battery-DNI. We found in children with dyslalias: A) The memory profile deteriorated globally in respect to the reference group but are preserved remote memory and the memory of shapes. B) kinesthesia and estereognosia disorders. C) Attentional disorders. We found mnemonic and attentional problems in children with dyslalias similar to those children with language problems secondary to brain damage or affect organs or major psycholinguistic disorders. We consider this neuropsychological profile deteriorated in neurological and psychoeducational counseling, which would justify the treatment and neuropsychological rehabilitation of memory and attention.